Challenges in translating interview protocols for alleged child victims of sexual abuse to different languages: A case study. (August 2019) - Navarro, Carolina; Knight, Tess; Sharman, Stefanie J.; Powell, Martine B.
Abstract: Adequate interviewing of alleged victims of child sexual abuse is critical for the investigation and for preserving the welfare of the child. Investigative interview protocols for children (IIPCs) have been developed to meet this twofold purpose. This article focuses on one previously unexplored issue related to applicability of IIPCs: how well they translate into other languages. This case study provides an in-depth analysis of an example of the translation of an IIPC to a new language and its adaptation to a particular cultural setting. Using an interpretive description approach and a mixed-method, stages and outputs of the adaptation process are described, as well as the amount, type and nature of difficulties in translation that were identified and corrected across the process. The main threats to translation equivalence arose from differences among languages, but also from cultural and contextual differences. Prompts to children and interviewers within the protocol presented different translation challenges. Consultation with experts and the protocol's advisors, along with team discussions, were beneficial in identifying and solving translation issues. Typical translation issues and practical recommendations on how to translate and culturally adapt IIPCs effectively are discussed.